1999
DOI: 10.1080/1028415x.1999.11747284
|View full text |Cite
|
Sign up to set email alerts
|

Taste Aversion Learning as a Tool for the Study of Hippocampal and Non-Hippocampal Brain Memory Circuits Regulating Diet Selection

Abstract: Diet selection is the result of different learning experiences that accumulate throughout the life of the organism. The acquisition of aversions to the taste of food followed by mild or severe visceral negative effects plays an important role in food selection. Current knowledge on the role of the critical brain areas (parabrachial area, insular cortex and amygdala) involved in the basic associative neural circuit of taste aversion learning is reviewed. In turn, as shown by a variety of learning phenomena, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 195 publications
0
9
0
1
Order By: Relevance
“…The authors attributed the delayed onset of latent inhibition to immaturity of the hippocampal system, since fornix transections performed in preweanling rats disrupted the emergence of latent inhibition at 32 days of age. However, at present, there is no evidence for a critical hippocampal involvement in latent inhibition of CTA (for reviews see Buhusi, Gray, & Schmajuk, 1998;Gallo, Ballesteros, Molero, & Morón, 1999). Lesion studies in adult rats showed no effect (Gallo & Cándido, 1995) or enhancement of latent inhibition (Purves, Bonardi, & Hall, 1995;Reilly, Harley, & Revusky, 1993).…”
Section: Discussionmentioning
confidence: 95%
“…The authors attributed the delayed onset of latent inhibition to immaturity of the hippocampal system, since fornix transections performed in preweanling rats disrupted the emergence of latent inhibition at 32 days of age. However, at present, there is no evidence for a critical hippocampal involvement in latent inhibition of CTA (for reviews see Buhusi, Gray, & Schmajuk, 1998;Gallo, Ballesteros, Molero, & Morón, 1999). Lesion studies in adult rats showed no effect (Gallo & Cándido, 1995) or enhancement of latent inhibition (Purves, Bonardi, & Hall, 1995;Reilly, Harley, & Revusky, 1993).…”
Section: Discussionmentioning
confidence: 95%
“…First, CTA can be acquired with a single pairing between the taste and the visceral discomfort [6,13,[22][23][24][25]. Second, conditioned taste aversion is an example of a biological predisposition to associate certain stimuli more easily.…”
Section: Description Of the Conditioned Taste Aversion Paradigmmentioning
confidence: 99%
“…These nuclei have complex connections with other structures; therefore it is thought that the activity of the amygdala is relevant in the modulation of some types of learning and memory [4]. In particular, the amygdala appears to participate in several complex processes underlying taste learning [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A critical feature adding complexity to taste sensation is the dynamic nature of the gustatory system, as it is modified by learning, even at the lower brainstem level (Yamamoto & Yasoshima 2007). Moreover, in spite of a general misconception about the low cognitive level of taste memory, it shows complex learning phenomena dependent on the hippocampal system (Gallo et al 1999), and it shares molecular mechanisms with other complex types of memories (Shema et al 2007).…”
mentioning
confidence: 99%
“…First, in conditioned blocking, previous training with an individual member of a compound modulates learning about another member of the compound. Thus, a previously learned aversion or preference to an individual taste A retards the acquisition of a new learned response to a different taste B if the later is presented in a compound AB (Balleine et al 2005; Gallo et al 1999). The blocking phenomenon would not appear if the compound had been sensed as singular and the individual basic components had not been recognized by the animals.…”
mentioning
confidence: 99%